International Arbitration in Indonesia after Constitutional Court Decision No. 100/PUU-XXII/2024: The Urgency of Resolving Enforcement Challenges - Yati Nurhayati; Ifrani; M. Yasir Said; Muhammad Hendri Yanova; Parman Komarudin (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2026)
Despite the issuance of Constitutional Court Decision No. 100/PUU-XXII/2024, legal uncertainty concerning the recognition and enforcement of international arbitral awards remains a significant challenge to the effectiveness of international arbitration in Indonesia. The particular study examined the legal implications of the Constitutional Court's removal of the term “deemed” from Article 1(9) of the Arbitration Law. Moreover, it proposed an ideal framework for determining the international character of arbitral awards under Indonesian law. The research employed a mixed method that combines normative legal research and case analysis through statutory, conceptual, case, and historical approaches. The findings revealed that Constitutional Court Decision No. 100/PUU-XXII/2024 has not fully resolved the legal uncertainty surrounding the distinction between domestic and international arbitral awards. While the decision reinforces a territorial approach based on the place where an award is rendered, it does not establish clear criteria for determining the international character of arbitral awards, thereby hindering the harmonization of their recognition and enforcement. The study further found that the Indonesian Arbitration Law remains inconsistent with the UNCITRAL Model Law on the definition and classification of international arbitral awards. To address this issue, the study proposed a broader territorial approach aligned with the UNCITRAL Model Law, incorporating international elements as determining factors, including the application of foreign law, the selection of foreign arbitral institutions or arbitrators, international civil legal relationships, and foreign elements within the factual circumstances of a dispute. This framework contributed to strengthening legal certainty and enhancing the recognition and enforcement of international arbitral awards in Indonesia.